Crop Reconstruction Surgery on Blue and Gold Macaws (Ara Ararauna) with Recurrent Crop Fistula - Nofan Rickyawan; Hazra Maulidina (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
A crop fistula is an abnormal tunnel in the skin and crop tissue due to damage to the crop wall. The causes are ingestion of foreign bodies, sharp objects, trauma, chronic irritation and crop burn. A female Blue and Gold Macaw (Ara ararauna), five months old and 0.75 kg body weight, came to the Teaching Veterinary Hospital, Universitas Brawijaya, due to dehiscence wounds with infection in the crop area. At first, the bird had crop fistula due to crop burn and had done an ingluviotomy procedure twice at another veterinary clinic but repeated dehiscence after surgery. Diagnosis based on history, clinical symptoms, physical examination and clinical findings is recurrent crop fistula. An ingluviotomy and debridement to clean and separate the skin and crop tissue. The principle of surgical procedure is to increase the healing potential of corrected healthy tissue. Surgical techniques and postoperative care should be optimal to ensure permanent wound healing and not cause recurrent dehiscence. The development of surgical wound healing improved until the 18th postoperative day, and neither dehiscence nor infection occurred.